Ethnomodelling as a polysemy of ethnomathematics - Zulma Elizabete de Freitas Madruga (Universitas Sarjanawiyata Tamansiswa, 2025)
Ethnomathematics values various forms of mathematical knowledge in different cultural contexts. This polysemic concept refers not only to different forms of knowledge, but also to the interconnection between these practices and other fields of knowledge. Ethnomathematics provides a perspective that respects cultural diversity and fosters a deeper comprehension of mathematics as an integral aspect of human activities. In that regard, this article discusses Ethnomodelling as a polysemy or conception of Ethnomathematics from an intercultural viewpoint. To do so, the concepts of Ethnomodelling and ethnomodels are introduced, along with their contributions to an intercultural Mathematics Education. Ethnomodelling is understood here as a theoretical-methodological construct, an emerging approach that connects Ethnomathematics to Mathematical Modelling based on ethnomodels, aiming to establish communication among different systems of mathematical knowledge and enabling intercultural comparisons and translations between local and global approaches. This research contributes theoretically by expanding Ethnomathematics through modelling processes, methodologically by proposing dialogical analysis between formal and informal mathematics, and practically by enhancing culturally responsive mathematics education.